Prevalence and Molecular and Antimicrobial Characteristics of Cronobacter spp. Isolated From Raw Vegetables in China - Ling, Na; Li, Chengsi; Zhang, Jumei; Wu, Qingping; Zeng, Haiyan; He, Wenjing; Ye, Yingwang; Wang, Juan; Ding, Yu; Chen, Moutong; Xue, Liang; Ye, Qinghua; et al. (Frontiers in Microbiology, 2018)
Cronobacter spp. is a foodborne pathogen that causes life-threatening and invasive diseases, such as necrotizing enterocolitis, meningitis, and sepsis. In this study, we aimed to investigate the prevalence, molecular characteristics and antimicrobial resistance of Cronobacter spp. in raw vegetables marketed in China. Based on dietary habits in China, 403 raw vegetables that could be eaten without additional cooking were collected. Of the 403 samples tested, 122 (30.27%) were positive for Cronobacter spp., and the contamination levels exceeded 110 most probable number (MPN)/g for 16.39% (20/122) of the samples. Coriander samples had the highest contamination rate of 52.81%, and the MPN values of 19.15% of positive coriander samples exceeded 100 MPN/g. Eleven serotypes were identified among 171 isolates, with Cronobacter sakazakii serogroup O1 (41 isolates) being the dominant serotype. Molecular characterization indicated that there was quite high genetic diversity in Cronobacter spp., and multilocus sequence typing analyses yielded 106 sequence types (STs), 55 of which were newly identified. Notably, the most prevalent ST (eight isolates) was C. malonaticus ST60, which appeared in a recent clinical infectious disease study in China. Five C. sakazakii ST4, seven C. malonaticus ST7, and three C. sakazakii ST8 confirmed as pathogenic sequence types in other countries were also detected in this study. Furthermore, all isolates were susceptible to amikacin, amoxicillin-clavulanic, cefepime, ciprofloxacin, and imipenem, but some isolates exhibited a high ratio of resistance to cephalothin (59.65%). In this study, the high contamination rate and the detection of pathogenic and new sequence types in raw vegetables indicated potential hazards to customers. To the best of our knowledge, this is the first report to provide valuable information on the contamination status of Cronobacter spp. in vegetables that can be eaten raw in China.